The Concept of Dignity and Its Use in End-of-Life Debates in England and France - Horn, Ruth ca. 20. / 21. Jh.; Kerasidou, Angeliki (2016)
Dignity is one of the most controversial and yet commonly used terms in debates regarding end-of-life issues. The term “dignity” can take various meanings. For example, it can be used to denote the respect owed to an individual person, or to signify the intrinsic value of humankind as a whole. These two different understandings of dignity inevitably lead to different approaches to end-of-life decisionmaking.This article explores the meaning of the term “dignity” in two European countries, England and France. Our analysis compares public debates and legislation on end-of-life-related issues in these two countries. We argue that in England dignity is most commonly understood as respect for individual autonomy, whereas in France dignity usually signifies respect for humanity as a whole. We demonstrate that the difference in the conceptualization of the term leads to different ethical, and hence legal and practical, approaches to end-of-life issues and vulnerable patients. Our particular focus is on (1) withdrawing/withholding life-sustaining treatment, (2) respect for patient preferences, and (3) assistance in dying.Given the difference in the understanding of dignity, and the underlying philosophical approaches, it appears that there is still a long way to go before we can establish common guidelines on end-of-life decisions across Europe and beyond. However, clarifying the use of the term “dignity” in different discussions around Europe could hopefully facilitate this endeavor.
Keywords: England; France; end-of-life decisions; Autonomy; Dignity